2020
DOI: 10.3390/microorganisms8040618
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Caenorhabditis elegans Responses to Pathogenic Microbiota

Abstract: The bacterivorous nematode Caenorhabditis elegans is an important model species for understanding genetic variation of complex traits. So far, most studies involve axenic laboratory settings using Escherichia coli as the sole bacterial species. Over the past decade, however, investigations into the genetic variation of responses to pathogenic microbiota have increasingly received attention. Quantitative genetic analyses have revealed detailed insight into loci, genetic variants, and pathways in C. elegans unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…To facilitate the study of natural diversity, hundreds of isolates of C. elegans have been collected from around the world [33]. These wild isolates have different levels of susceptibility to pathogens and natural variants have been discovered that impact traits such as bacterial avoidance and viral susceptibility [7,19,[34][35][36][37]. Although studying phenotypic variation in wild isolates is a powerful approach, measuring each strain individually is time-consuming and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the study of natural diversity, hundreds of isolates of C. elegans have been collected from around the world [33]. These wild isolates have different levels of susceptibility to pathogens and natural variants have been discovered that impact traits such as bacterial avoidance and viral susceptibility [7,19,[34][35][36][37]. Although studying phenotypic variation in wild isolates is a powerful approach, measuring each strain individually is time-consuming and laborious.…”
Section: Introductionmentioning
confidence: 99%
“… 32 , 33 The worm has also been extensively used in the field of host-pathogen interaction, triggering the regulation of innate immunity 34 as well as a cascade of a wide variety of genes. 35 Similarly, Drosophila has been extensively used as a model to study the phenomenology and the underlying molecular and cellular mechanisms of microbiota-diet interactions and their influence on host biology including postnatal development (ie juvenile growth and maturation), adult physiology (ie immune and metabolic functions and behavior) and aging. 36 , 37 …”
Section: Part a Methods For Studying The Causal Role Of Gut Microbiotamentioning
confidence: 99%
“…By comparing viral susceptibility in three different backgrounds, Bristol N2, JU1580, and JU1511, we found that the genetic background may influence the interaction effect of HS and viral infection. It is well known that a different genetic background can have strong differential effects on complex phenotypes [34,35] and that even the phenotypic effects of strong single gene mutations can be modulated. Our results suggest that the genetic background may also have genetic modifiers that can modulate the effect of viral infection in combination with HS.…”
Section: Hs Effects On Orv Viral Load May Depend On the Genetic Backgroundmentioning
confidence: 99%